Creating customer preferences for online marketplace promotional strategy: a survey of youth in Malaysia during the COVID-19 pandemic / Rahmandika Adipradana … [et al.] - Adipradana, Rahmandika; Dharmawan, Dhiyaa Calista; Zhucheng, Shao; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2023)
Our research focuses on creating customer preferences and a promotional strategy towards the online marketplace among adults in Malaysia during the Covid-19 outbreak. The purpose of this study is to analyze the factors creating customer preferences for a promotional strategy towards the online marketplace in Malaysia, with our focus on youth between 18 and 25 years old. We focus on analyzing the relationship between discount and customer preferences, the relationship between advertising and customer preferences, and the relationship between coupons and customer preferences. Discounts, advertising, and coupons all serve as independent variables in this study. Consumer preferences are the dependent variable.